Quickstart for toddlers with autism spectrum disorder: A preliminary report of an adapted community-based early intervention program. (November 2022) - Gaines, Robin; Korneluk, Yolanda; Quigley, Danielle; Chiasson, Véronique; Delehanty, Abigail; Jacobson, Suzanne
Background and Aims: Early intervention (EI) for young children with autism spectrum disorder (ASD) must be resource-efficient while remaining effective; thus, clinicians are challenged to create and implement useful methods. Clinical evidence from community-based interventions that include reliable diagnoses, individual EI programs, along with comprehensive descriptions of participants, procedures, and participant outcomes can inform practice, translational research, and local policy. Parent-mediated EI for toddlers with ASD can promote positive developmental outcomes and lifelong well-being, but evidence of successful community uptake of research-based EIs is somewhat limited. The community-based, parent-mediated, evidence-informed QuickStart EI program aims to encourage toddlers' early social communication, social interactions, and relationship-building, in a community clinic setting. We aim to (1) describe our adaptations to the evidence-based Parent-Delivered Early Start Denver Model and (2) present promising findings for toddlers with or at risk for ASD and their families who received QuickStart. We also intend to motivate a similar study of EI in real-world situations to advance evidence-based practice and create relevant dialogue and questions for research. Methods: Complete data were identified and analyzed for up to 89 toddlers diagnosed with, or at risk of, ASD. Pre- and post-intervention parent- or self-report data were analyzed using descriptive statistics and paired-sample t- tests, as appropriate. Pre-intervention measures included demographic information ( n = 89) and the Early Screening of Autism and Communication (ESAC; n = 89). Measures taken pre- and post-intervention included the Adaptive Behavior Assessment System-II ( n = 60), MacArthur-Bates Communication Development Inventories ( n = 58), and the parental sense of competence scale ( n = 62). The Measure of Processes of Care ( n = 60) was taken post-intervention. On enrollment, parents signed standard clinical agreements that included statements allowing their anonymous data to be analyzed for research. Results: Using standardized parent/self-report measures, toddler gains were noted for social interaction, language, communication skills, and ASD symptoms, but not for parents' feelings of competence. Parents identified QuickStart procedures as family centered (Measure of Processes of Care). Conclusions: The QuickStart EI program, provided to toddlers and their families over 20 weeks in a community clinic, resulted in promising positive behavior and communication changes, as indicated on the parent-response measures, for a moderately large sample of toddlers. Implications: This study adds to the literature by describing a new EI program with clear procedures by which clinicians can create, provide, and evaluate a readily accessible, community-based EI for toddlers with or at risk of ASD. Methodological limitations inherent to our study design that precluded a control group and necessitated a reliance on available parent-report data are carefully critiqued and discussed.